Pengaruh Influencer, Kualitas Produk & Impulse Buying terhadap Keputusan Pembelian Skincare Somethinc - Khofiyyan, Nida Nur (Jurnal Dimamu, 2025)
Based on the results of research that is against the background of the rapid development of the times at this time, local brand skincare products are increasingly in demand by a wide audience, one of which is the local skincare brand Somethinc. This study aims to find out how influencers, product quality & impulse buying influence on Somethinc skincare purchase decisions. The object of this study is Somethinc product users who also know influencer Tasya Farasya on TikTok. The type of research is using quantitative methods with primary and secondary data types using data collection techniques in the form of distributing questionnaires. In this study, a Non-Probability Sampling technique was used with an unknown population and a sample of 100 people. The results of this study show that there is a significant influence between influencer variables on purchase decisions of 8.10%. There was a significant influence between product quality variables on purchase decisions by 18.3%. There was a significant influence between the impulse buying variable on the purchase decision by 10.2%. And simultaneously there was a significant influence between influencer variables, product quality, and impulse buying on purchase decisions by 126.9%.